Effectiveness of Interpersonal Psychotherapy on Relationship Satisfaction and Anxiety in Women with Rejection Sensitivity - Camilo Ríos, Juan; Hernández, Carlos; Abalorio, Bridget (Psychology of Woman Journal, 2024)
Objective: This study aimed to evaluate the effectiveness of Interpersonal Psychotherapy (IPT) in improving relationship satisfaction and reducing anxiety among women with high rejection sensitivity.Methods and Materials: A randomized controlled trial design was implemented with 30 women from Mexico who met the criteria for elevated rejection sensitivity. Participants were randomly assigned to either an experimental group (n = 15) receiving 12 weekly sessions of IPT or a waitlist control group (n = 15). Assessments were conducted at three time points: pre-test, post-test, and five-month follow-up, using the Couples Satisfaction Index (CSI-32) to measure relationship satisfaction and the Beck Anxiety Inventory (BAI) to assess anxiety. Data were analyzed using repeated measures ANOVA with Bonferroni post-hoc tests in SPSS-27 to evaluate within-group and between-group changes over time.Findings: Repeated measures ANOVA revealed significant interaction effects between time and group for relationship satisfaction (F(2,28) = 60.89, p < .001, η² = .81) and anxiety (F(2,28) = 55.28, p < .001, η² = .79). Bonferroni post-hoc tests indicated that the IPT group experienced a significant increase in relationship satisfaction from pre-test to post-test (p < .001) and follow-up (p < .001), with no significant decline at follow-up (p = .109). Similarly, anxiety levels significantly decreased from pre-test to post-test (p < .001) and remained stable at follow-up (p = .356), while no significant changes were observed in the control group.Conclusion: The results suggest that Interpersonal Psychotherapy is a highly effective intervention for enhancing relationship satisfaction and reducing anxiety in women with rejection sensitivity. The therapeutic gains were not only significant immediately after the intervention but were also sustained at the five-month follow-up, indicating long-term benefits of the approach.